Aplikasi Wisata Berplatform Android dengan Teknologi QR Code - Afan Galih Salman (Bina Nusantara University, 2013)
As a country renowned for its natural beauty, Indonesia has many interesting attractions to visit. An example is the attraction of animals shown at Ragunan Zoo. At Ragunan Zoo visitors not only enjoy the tour, but also learn about animals shown. However, information about the animals is only provided on the board. Therefore,Ragunan Zoo needs a technology that provides more information, efficiently and as a guide to explore the tourist attractions. The purpose of this research is to design an android-based mobile application that can provide information more than what is show on the board as well as provides digital mapinformation. The application generated in this study implements the QR code scanning to obtain information as well as locations of digital map attraction.